Analisis Pentingnya Kode Etik Public Relation dalam Menjaga Citra Perusahaan - Efendi, Erwan; Hsb, Saima Putri; Siregar, Salsa Fadilah; Harahap, Yuli Awanda; Br Purba, Endah Rananda Gita; Harahap, Muhammad Yasim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Public Relations (PR) plays a crucial role in the success of a company. PR helps shape the positive image of the company in the eyes of the public, maintains good relationships with customers and stakeholders, supports marketing strategies, and safeguards the company's reputation in times of crisis. This research uses the Literature Review method. With this method, the research will delve into the concepts contained in the PR code of ethics, such as honesty, integrity, and social responsibility. Literature Review will provide a deep understanding of the ethical values that form the basis for maintaining and building a positive company image. The research shows that Advertising Experts, as one of the links between an organization and its public, certainly have rules to follow. These policies are related to the morals and ethics that must be upheld by a PR professional in supporting their work. Advertising morals are used as a guideline for the skills and thinking that leave an impression on an Advertising specialist in their actions and decision-making. An Advertising Specialist certainly has responsibilities and obligations that play a crucial role in the organization's image.